Students' pride orientation in a learner-focused school setting - Judith Fraenken; Marold Wosnitza (EARLI, 2019)
In the past decades, schools have become more autonomous and open learning environments. It therefore seems increasingly important for educational research to also consider contextual influences by including autonomous learning settings in its investigations. Studying the positive activating emotion of pride seems useful to learn more about the effects of this schooling as pride results from exactly those aspects promoted by autonomous learning: Self-evaluation, reflection, self-responsibility and attribution. Moreover, pride becomes relevant for a deeper understanding of students' learning and achievement as pride promotes the desire to repeat already performed achievements in the future. Regarding the growing support of individual learning in schools, the present study investigates objects of pride of students attending a school that promotes autonomous, non-competitive, individualized and cooperative learning. Students of this school plan their timetables and learning process individually and document it in learning logbooks in which they furthermore can state once a week what they are proud of. In total, 1063 pride statements from 134 students were collected from the learning logbooks. A complementary study, collecting students' pride statements detached from the learning logbooks, identified 254 pride statements. Results show that the pride focus of students at the examined school is learning-oriented. The findings indicate that the specific learning setting of the examined school provides specific school-based pride triggers and thus promotes the learning-oriented pride focus of the students. This paper shall serve as a basis for further research on students' pride and objects of pride and its potential effects on motivation, achievement and school life.